The Financing of Industry, 1970-89: An International Comparison. - Corbett, J; Jenkinson, T (CEPR, 1994)
The main aims of this paper are, first, to construct a consistent comparative set of data on the sources of finance for investment over the period 1970--89 for Germany, Japan, the United Kingdom and the United States and second, to challenge some conventional views of the international differences in financing patterns. The paper documents the substantial problems of international comparisons, and argues that net sources and using data based on National Income Accounts provide the most appropriate and consistent information. We conclude that there is no 'market-based' Anglo-US pattern of financing of industry. Germany, the United Kingdom and the United States are internally financed with small or negative contributions from market sources. Japan has been more externally financed with both banks and markets contributing larger shares than in the former group. Over the 1980s, the period of financial liberalization, all countries, except Japan, have become more internally and less market financed.